The Effect of Height on Earnings : Is Stature Just a Proxy for Cognitive and Non-Cognitive Skills? - Bossavie, Laurent (World Bank, Washington, DC, 2017)
This study investigates the degree to which the association of height and earnings in Pakistan is independent of other cognitive and socioemotional skills. While taller workers are regularly observed to earn more, they commonly have higher cognitive ability. Thus, there is debate concerning the independent contribution of stature. The study explores the relationship between height and earnings when a measure of cognitive ability -- performance on Raven's matrices -- and an index of socioemotional capacity are included. The study finds that there is only modest attenuation of the coefficient of height—treated as endogenous or exogenous—when these additional indicators of human capital are included.